Полевая мышь (Apodemus agrarius Pall.) в условиях Украины. Сообщение II. Колебание численности - Свириденко, П.А. (Вестник зоологии, 1972)
The article deals with the results of studying the variation in Apodemus agrarius Pall. quantity in the reservation Aleksandriya (the Kiev region). The investigation was carried out from the autumn of 1947 till 1954. The data on other areas of the USSR are also given. It is established that in Apodemus agrarius Pall. annual variations in the quantity are less pronounced than in other Muridae- Microtus aralis Pall., M. so-calls Pall. and Mus musculus Li seasonal variations in its quaftily are very sharp. Apodemus agrarius Pall. belongs to hygrophilic and thermophilic rodents, that is why meteorological conditions in the habitals, besides abundance of food, are main factors delermining its viability and intensily of reproduction. In winter a catastrophic reduction in a number of the animals in a population takes place (in some years only 08-4.8% of the aulumn quantity of the animals remained by spring). Early warm spring. humid summer and warm long aufumn favour a sharp increase in a number of Apodemus agra-rius Pall. * Работы, приведенные в сообщения | (Свириденко, 1971). в данный список не включены.